Venous Thromboembolism in Women of Childbearing Age: Insights from the START Registry - Grandone, Elvira; Antonucci, Emilia; Colaizzo, Donatella; De Laurenzo, Antonio; Cosmi, Benilde; Cini, Michela; Legnani, Cristina; Testa, Sophie; Margaglione, Maurizio; Palareti, Gualtiero (Thrombosis and Haemostasis, 2023)
Background Women of childbearing age are exposed to venous thromboembolic risk mainly for pregnancy and use of oral contraceptives. The impact of risk factors (RF) on venous thromboembolism (VTE) in these circumstances is still unclear.Aim In the context of START registry, we aimed to investigate the weight of a series of RF on the occurrence of pregnancy- or combined oral contraceptive (COC)-associated VTE.Materials and Methods We selected all women included in the START for VTE occurred between 18–42 years and compared those with a first or recurrent pregnancy/postpartum- (group A) or COC-VTE (group B) with those who had VTE outside these circumstances (group C). Final analysis included a cohort of 532 women. Follow-up data showed that there were no significant differences between the groups in terms of thrombotic and haemorrhagic complications. As for pregnancy-associated VTE, the overall outcome was good in terms of both maternal and fetal prognosis.Results In a binary model of logistic regression, correcting for potential confounders, VTE family history conferred a significant and independent higher risk of COC-VTE compared with group C. Similarly, comparison between group A and C documented that family history significantly affected the risk of pregnancy-associated VTE. VTE in the group C was significantly associated with older age. Lastly, smoke was a significant risk factor for pregnancy/postpartum VTE when group A and group B were compared.Conclusion Present data suggest that in the setting of fertile women, family history of VTE has a greater role in predicting COC- and pregnancy/postpartum- VTE than outside these circumstances.
Keywords: oral contraceptives; pregnancy; postpartum; venous thromboembolism